An Overview on Novel Drug Delivery System of Microsphere and its Types, Materials, Method of Preparation - Joshi, Varda; Velhal, Atish; Patil, Swapnali; Redasani, Vivekkumar; Raut, Poonam; Bhosale, Nikita (Asian Journal of Pharmaceutical Research and Development, 2023)
Today, there is a lot of interest in medication delivery systems based on microspheres. Microspheres can be created using both natural and artificial polymers and are typically free-flowing powders. The microspheres' diameters range from 1 to 1000 m. In microspheres, the medicine is evenly spread, dissolved, or suspended in a matrix system. Drugs that are either solid or liquid are dissolved or disseminated in a matrix system in microspheres. The current review gives a thorough overview of recent and innovative advancements on microsphere forms that have been claimed to boost bioavailability, improve stability, lengthen biological half-life, and lessen drug toxicity. Many different proteins and peptide compounds can be delivered effectively by microsphere. Microspheres come in a variety of forms, including bioadhesive, magnetic, polymeric, floating, and floating microspheres. In order to create microspheres, a variety of techniques are employed, including simple emulsion-based, double emulsion-based, interfacial deposition, interfacial polymerisation, phase separation, and spray drying. Through a variety of delivery methods, including oral, topical, naso-pulmonary, and gene therapy, microspheres administer the medication in a regulated manner. Due to their ability to encapsulate a variety of medications, biocompatibility, high bioavailability, and continuous drug release nature, polymeric based microspheres serve as ideal carriers for several controlled delivery applications. As a result, by creating novel procedures, it can increase therapeutic results and enhance drug safety. The development of microspheres has been linked to improvements in the drug's stability, bioavailability, biological half-life, and toxicity.